2014
DOI: 10.1210/en.2013-2006
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3 Is Critical for Coxsackievirus B4-Induced Type 1 Diabetes in Female NOD Mice

Abstract: Group B coxsackieviruses (CVBs) are involved in triggering some cases of type 1 diabetes mellitus (T1DM). However, the molecular mechanism(s) responsible for this remain elusive. Toll-like receptor 3 (TLR3), a receptor that recognizes viral double-stranded RNA, is hypothesized to play a role in virus-induced T1DM, although this hypothesis is yet to be substantiated. The objective of this study was to directly investigate the role of TLR3 in CVB-triggered T1DM in nonobese diabetic (NOD) mice, a mouse model of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 63 publications
3
48
0
Order By: Relevance
“…There was not diffrence between the genotypes either in the baseline Log 10 (C q ) level at 5 weeks ( P > 0.2) or in the rate of change over time ( P > 0.2), indicating no effect of genotype on average CXCL10 expression. These results were as predicted, based on our previous research that has shown no difference in the incidence of diabetes in uninfected TLR3 / vs TLR3 +/+ NOD mice (10). Observations were plotted, with model best-fit regression line in blue, with the gray shading representing the 95% confidence interval (Supplementary Figure S3).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…There was not diffrence between the genotypes either in the baseline Log 10 (C q ) level at 5 weeks ( P > 0.2) or in the rate of change over time ( P > 0.2), indicating no effect of genotype on average CXCL10 expression. These results were as predicted, based on our previous research that has shown no difference in the incidence of diabetes in uninfected TLR3 / vs TLR3 +/+ NOD mice (10). Observations were plotted, with model best-fit regression line in blue, with the gray shading representing the 95% confidence interval (Supplementary Figure S3).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, we wanted to investigate if there was a difference in expression of CXCL10 between wild-type (TLR3 +/+ ) and TLR3-deficient (TLR3 / ) NOD mice in the pre-diabetic stage. We predicted that CXCL10 levels should be similar in both sets of animals that have not been exposed to virus since the insulitis scores of both sets of animals were the same in our previous study (10), as was the rate of development of spontaneous diabetes (9, 10). …”
mentioning
confidence: 84%
See 1 more Smart Citation
“…It is interesting that TLR3−/− had no influence on spontaneous diabetes development in NOD mice [97] whereas TLR3 was indispensable for virus-induced diabetes in NOD [118, 119] or BALB/c mice [120] and in BB rats [121, 122]. Therefore, changing how these innate immune receptors interact with the environment is important for altering susceptibility to or protection from diabetes.…”
Section: The Role Of the Gut Microbiota In Modifying Diabetes Suscmentioning
confidence: 99%
“…However, further examination of the role of TLR3 signaling in glucose metabolism and diabetes merits consideration. In fact, the association between TLR3 and glucose metabolism has been recently proposed [50,31]. Moreover, reports show that polymorphisms in the TLR3 gene are associated with risk for type 1 diabetes [36,5].…”
Section: Discussionmentioning
confidence: 97%